Comparison of Caffeine and Aminophylline in Treating Apnea of Prematurity with Historical Data: A Single Center, Observational Study in Taiwan - Fong-Cheng Ho; Tsai-Hui Duh; Hao-Wei Chung; Shu-Ting Yang; Hsiu-Lin Chen (Iranian Journal of Neonatology)
Background: For treatment of apnea of prematurity (AOP), aminophylline is the first line medication in Taiwan. There are limited trials in Taiwan regarding the therapeutic benefits and adverse effects of caffeine for the treatment of AOP.Methods: This observational study conducted between January 2018 and December 2018 investigated the clinical effectiveness and safety of caffeine for AOP in the neonatal intensive care unit (NICU) at a hospital in Taiwan. Very preterm neonates with very low birth weight and apnea were treated with a loading dose of caffeine citrate at 20 mg/kg, followed by a 5–10 mg/kg maintenance dose every 24 h. Preterm infants admitted to the NICU between January 2017 and December 2018 and treated with aminophylline/theophylline were included for comparison.Results: Seventeen infants receiving caffeine therapy and 43 receiving aminophylline/theophylline therapy were enrolled in this study. Although fewer apneic spells were observed from the second week of commencing caffeine treatment (P=0.028), the mean duration of apnea and episodes of apneic spells during the first four weeks of treatment were similar between the two groups. There were no significant differences in short-term side effects, duration of intubation, noninvasive respiratory support, hospitalization, and medical expenses between the two groups.Conclusion: Caffeine treatment can reduce the frequency of apnea after one week of administration; however, both caffeine and aminophylline/theophylline showed similar effects in treating AOP.